EFL CRITICAL READING SYLLABUS AND MATERIALS FOR STUDENTS OF THE ENGLISH DEPARTMENT - Imran, Fathurrahman; Hidayatullah, Heri (IKIP Mataram, 2020)
The demand of a new model of syllabus and materials were implicitly required through the launching of KKNI-based Curriculum in Indonesia. Due to, finding the students? needs and learning characteristic as the main consideration in developing them became the purpose of this current research. A qualitative research had been conducted to get the data needed by which two kinds of questionnaires were administered then analyzed qualitatively (Likert scale). The respondents involved were 132 students and the results dealt with the learning characteristics showed that the audio was 19.69%, the visual was 50.75%, and kinaesthetic was 29.54%. In relation to the students? needs (four aspects), 1) necessities on topic interest like education (72%), culture (63%), and social life (45%); 2) background knowledge was categorized into good (57.25%), very good (28%), and not good (14.75%); 3) critical reading goals for both core and sub-skills very agree (42.71%), agree (30.14%), and not agree (27.14%); and 4) learning model tended the cooperative (27.25 very agree), (35.5 agree), (37.25 not agree). Thus, it could be concluded that the students? learning style dominantly in visual way with cooperative learning model. In addition, the students were eager to have critical reading skills with sufficient prior knowledge but the topic is mostly in the area of education. It is recommended that in developing the syllabus and materials, the lecturers should consider both students? characteristics and needs.